Modeling and simulation of crude distillation unit (CDU) - Shu Yin, Oh (2014)
There is rapid growth in the usage and demand of crude oil in various industrial fields. Thus, the price of the petrol is rising due to the stronger-than-expected demand for petroleum products. Nowadays, simulation has become an important tool in the behavior study of almost all chemical processes. A proper modeling can bring great advantages to an industry, among them, the increase in knowledge about the process without the need to carry out the real processes. A good model is necessary to develop a proper control strategy for crude distillation unit (CDU) as it can provide more accurate behaviour study of the real system. Due to the lack of proper simulation of CDU, this research is aimed to develop modeling and simulation of CDU. Data of crude oil, the operating conditions of the involved units, and other essential data were collected and entered into the simulation software, Aspen Plus to generate the CDU model. The completed simulation of CDU was run and the results were studied. By solving model equations, the effect of different operating conditions of petroleum refining towards the yield and composition of petroleum products was determined. The higher the feed flow rate, the higher the products feed flow rates. To ensure the simulation is working, the results obtained were compared to previous works done by other researchers and were proven to be valid. Various information about the system under study were obtained easily using the CDU simulation model. The objectives of this research were accomplished